Bold risk behavior and involvement in commercial sex among adolescents: Systematic review - Putri, Nodeya Harda; Abdullah, Asnawi; Mainita, Mainita (Alma Ata University Press, 2025)
Background: The prevalence of adolescent involvement in prostitution has grown in the millennial era, often driven by lifestyle demands, economic pressures, and environmental influences. Despite various preventive and repressive government efforts, the phenomenon persists, affecting adolescents' physical and mental health and posing significant risks to future generations.Objectives: This study aims to explore the factors contributing to risky behaviors and adolescent involvement in commercial sex, highlighting the roles of external environments, media, alcohol, education, and financial pressures.Methods: A systematic review was conducted using the PEOs framework, analyzing articles from databases like PubMed. Inclusion criteria included original peer-reviewed articles published between 2014 and 2024 in English or Indonesian, focusing on risky behaviors and adolescent involvement in commercial sex. Exclusion criteria eliminated grey literature and non-research-based articles. Eleven articles were rigorously selected for critical appraisal and numerical assessment.Results: Findings reveal that family dysfunction, peer pressure, and media influences significantly shape adolescent behavior. Alcohol consumption impairs decision-making, increasing vulnerability to exploitation. Educational attainment correlates with risk, as adolescents with limited education are more prone to engage in risky behaviors. Financial pressures further drive adolescents toward commercial sex as a perceived solution to economic challenges.Conclusions: Adolescent involvement in commercial sex results from a confluence of external and internal factors, emphasizing the need for holistic interventions. Addressing family dynamics, enhancing educational opportunities, monitoring media exposure, and providing economic support can mitigate these risks. Comprehensive, multidisciplinary strategies are critical to protecting adolescent well-being and reducing the prevalence of risky behaviors